Saṅgharsha hī jīvana haī : saṃsmr̥tiyām̐ - Cauhāna, Harirāma, 1925-; Mādhava, Sañjaya; Communist Party of India (Marxist). Rājya Kameṭī, Rājasthāna (Jayapura : Bhāratīya Kamyunisṭa Pārṭī (Mārksavādī), Rājya Kameṭī, Rājasthāna, 2014)
Memoirs of Harirāma Cauhāna, born 1925, leader of Communist Party of India (Marxist) from Rajasthan, chiefly on political conditions and activities in Rajasthan.
In Hindi.
Keywords: Cauhāna, Harirāma, -- 1925-; Communist Party of India (Marxist). -- Rājya Kameṭī, Rājasthāna.; Rajasthan (India) -- Politics and government -- 20th century; Politics and government; India -- Rajasthan; 1900-1999